Alternanthera bicolor Produces Hypoglycemic Effect in Alloxan-Induced Diabetic Mice through its Antioxidant Activity (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The current investigation was carried out to evaluate the antioxidant properties of ethanolic extract of Alternanthera bicolor and to assess the potential hypoglycemic effect of the extract in alloxan-induced diabetic mice. HPLC-DAD method was used to determine polyphenolic compounds present in the extract. Different in vitro assays (i.e. DPPH radical scavenging activity test, reducing power test, NO radical inhibition assay and scavenging of hydrogen peroxide) were used to determine the antioxidant potential of the plant. Antidiabetic activity was evaluated in alloxan-induced diabetic mice by glucose tolerance test and standard biochemical analyses. HPLC-DAD analysis of the extract confirmed the presence of (+)-catechin hydrate, caffeic acid, quercetin and kaempferol. A. bicolor showed potent antioxidant activities in DPPH radical, hydrogen peroxide and nitric oxide scavenging assays. Moreover, A. bicolor showed potent reducing power and dose-dependent increment of total antioxidant capacity. Furthermore, the plant showed potent hypoglycemic activities in alloxan-induced diabetic mice. Ethanolic extract of the plant at doses of 200- and 400-mg/kg body weight (administered orally for 3 weeks) significantly decreased the elevated levels of blood glucose, lipid peroxidation product TBARS, hydroperoxides and nitric oxide in experimental animals. Apart from these activities, the ethanolic extract of the plant restored the reduced catalase function in liver. From this study, we can conclude that ethanolic extract of A. bicolor exhibited hypoglycemic and antioxidant activities in alloxan-induced diabetic mice.Dhaka Univ. J. Pharm. Sci. 18(1): 49-60, 2019 (June)